Speculative Revisions of Film History: A Curator’s Notes - Rasha Salti (Revue des Mondes Musulmans et de la Méditerranée)
Between the generation of experimental film makers of the 1960s and 1970s in the Arab world and that of the video makers of the 2000s, there is a generation of authors who have been consecrated and acclaimed regionally and internationally. The films produced by the first generation are very rarely shown, if ever, and most of them, particularly those produced by the most eccentric and most experienced artists, have fallen into obsolescence. In other words, there has been no significant transmission of experience through time or space. While attempts to trace shared sensibilities and extract resonances may be a subjective academic exercise, the reading or deconstructing of films within the context of shared cultural poetics is not an entirely useless or meaningless speculative exercise. The three installments (2010-2012) of Mapping Subjectivity: Experimentation in Arab Cinema from the 1960s to Now, presented at the Museum of Modern Art in New York were an embodiment of such an exercise. Our study is a reflection based on field research, and motivations behind the program’s selections.